Revision of the soft scale genus Paralecanium (Hemiptera: Coccomorpha: Coccidae) with the introduction of three new genera and twenty new species - Hodgson, Chris J.; Williams, Douglas J. (Zootaxa, 2018)
The soft scale insect genus Paralecanium Cockerell (Hemiptera: Coccomorpha: Coccidae), mainly characterised by the possession of fan-shaped marginal setae, has never been revised and most of the species currently recognised were described in the early part of the twentieth century. The present revision is based on the morphology of the adult females and redescribes and illustrates all 34 species or subspecies previously included in the genus. These three subspecies have been raised to full specific rank, namely P. expansum javanicum (Green) to P. javanicum (Green) stat. n.; P. expansum rotundum (Green) to P. rotundum (Green) stat. n. and P. frenchii macrozamiae (Fuller) to P. macrozamiae (Fuller) stat. n. Of the remaining previously recognised species, three have been made junior synonyms: P. album Takahashi is here considered to be a junior synonym of P. metallicum (Green), syn. n.; P. angkorense Takahashi is considered to be a junior synonym ofP. cocophyllae Banks, syn. n.; and P. limbatum Green is considered to be a junior synonym of P. geometricum (Green), syn. n. Paralecanium marianum Cockerell from Brazil is clearly not closely related to Paralecanium and so a new genus, Mariacoccus Hodgson & Williams gen. n., has been introduced to take it and the adult female is redescribed and illustrated; comparison of the adult female of M. marianus with that of Coccus lizeri (Fonseca) showed that the latter species is a junior synonym of M. marianus (Cockerell), syn. n. Based on the morphology of the above species and on the new species mentioned below, two new genera have been introduced: Insularicoccus Hodgson & Williams gen. n. (type species P. carolinensis Beardsley), and Discochiton Hodgson & Williams gen. n. (type species D. martini Hodgson, spec. n.). This brings the number of soft scale genera with fan-shaped marginal setae to three. Diagnoses of each of these 3 genera are presented, along with a key to the genera based on adult female morphology. The species that have been left in Paralecanium Cockerell are: P. calophylli (Green), P. frenchii (Maskell), P. geometricum (Green), P. hainanense Takahashi, P. machili Takahashi, P. macrozamiae (Fuller), P. maculatum Takahashi, P. marginatum (Green), P. maritimum (Green), P. minutum Takahashi, P. neomaritimum Takahashi, P. ovatum Morrison, P. pahanense Takahashi, P. peradeniyense (Green), P. planum (Green) and P. zonatum (Green). The species transferred to Discochiton as comb. n. are: P. album Takahashi, P. cocophyllae Banks, P. expansum (Green), P. javanicum (Green), P. luzonicum Cockerell, P. malainum Takahashi, P. mancum (Green), P. metallicum (Green), P. milleri Takahashi, P. pseudexpansum (Green), P. quadratum (Green), P. rotundum (Green),P. trifasciatum (Green) and P. vacuum Morrison. The only species transferred to Insularicoccus is the type species, namelyP. carolinense (Beardsley), comb. n. In addition, adult females of the following 11 new species are described and illustrated in the genus Paralecanium (as defined here) spec. n.: P. acinaces Hodgson, P. busoense Hodgson, P. claviseta Hodgson, P. comperei Hodgson, P. cypripedium Hodgson, P. elongatum Hodgson, P. leei Hodgson, P. morobeense Hodgson, P. neoguineense Hodgson, P. palawanense Hodgson and P. vacerra Hodgson. In addition, the following 8 species are described and illustrated as Discochiton spec. n.: D. browni Hodgson, D. crenulatum Hodgson, D. diplodiscus Hodgson, D. martini Hodgson, D. papillatum Hodgson, D. paucipedis Hodgson, D. sarawakense Hodgson and D. seychellarum Williams & Hodgson, and 1 species of Insularicoccus is described as new and illustrated, namely I. syzygium Hodgson spec. n. Keys, based on adult female morphology, are provided for separation of all the species in each genus. As part of this revision, the morphological characters used to diagnose species in this group of genera are re-evaluated and a number of new characters found; greater emphasis has been placed on some character-states, so the basic morphology of this group of genera is also described. Lectotypes have been designated for 22 species, namely: Lecanium calophylli Green; L. expansum Green; L. expansum javanicum Green; L. expansum metallicum Green; L. expansum rotundum Green; rotundum Green; L. geometricum Green; L. limbatum Green; L. mancum Green; L. marginatum Green; L. maritimum Green; L. peradeniyense Green; L. planum Green; L. pseudexpansum Green; L. quadratum Green; L. trifasciatum Green and L. zonatum Green. Also: Paralecanium album Takahashi; P. hainanense Takahashi; P. malianum Takahashi; P. marianum Cockerell; P. neomaritimum Takahashi and P. vacuum Morrison. Finally, an example of the first-instar nymphs, second-instar males and second/third instar females of both Paralecanium and Discochiton are described and illustrated and compared with those already known in the tribe Paralecaniini.